ECONOMIC SECURITY OF CORPORATIONS AS A MANAGED SYSTEM IN THE CONDITIONS OF NEO-INDUSTRIALIZATION (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The essence of neoindustrialization of society is considered. The features of economic safety of corporations as a managed system are determined. The resource and stakeholder component of interests harmonization is offered, thus forming the market value of the client and ensuring the economic security of corporations.An important role in assessing the relevance of the economy to neo-industrial requirements are the following factors: the ratio of research and development costs to GDP; the share of Internet users as an indicator of labor force education, the availability of information infrastructure and the availability of knowledge; share of tertiary sector in GDP.Ukraine belongs to the countries of the fourth cluster, that is, with an average degree of neo-industrialization. The purpose of the work is to determine the economic security of corporations as a managed system in Ukraine with neo-industrializationDeeper and more frequent crises, shortages of resources and ideas, increased raiding in the market necessitate a revision of approaches to the problem of ensuring economic security of the country. Since corporations determine the development of the economy of any state, they experience this influence.Corporations' economic security is a dynamic, nonlinear system of ordered, interconnected and managed elements (goals, structures, functions, processes), the consistent combination of which forms the resource and stealth components to identify, prevent and neutralize threats with available resources and efficient business process management. corporations, which forms the market value of the client. The economic security of corporations is a complex system, which consists of two system-forming elements: managed and control systems. As a result, their interaction generates system-wide qualities, that is, the features that are inherent in the system as a whole, and in particular each of them. The properties of control and control systems determine their place in the internal configuration of the system and implemented in its functions.Under the managed system, corporate economic security is a business process that affects a set of core, service and auxiliary business processes that use resources and ensure the harmonization of stakeholders' interests and the steady balance of all corporations.
Keywords: neoindustrialization, corporation, business process, resources, stakeholder, customer value